Features of the use of transmedia technologies in advertising communication - Yessenbekova У.М.; Takhan С.Ш. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2020)
The article explores new forms and features of the use of transmedia technologies in the advertising market and advertising communications in the media space. Advertising promotion mechanisms studied through media channels using information technology. The concepts of transmedia and the development of the information and communication industry are analyzed. The recommendations were made to improve the information and communication potential of society. Considered current trends in the market of advertising communications; ways of using transmedia technologies; the importance of advertising and transmedia strategies, their influence on the audience; the place of advertising studied in media activities. The author used different methodologies to determine and predict the development of advertising communications. The possibility of increasing the effectiveness of advertising communications, taking into account the peculiarities of the national mentality, is argued. Under these conditions, advertising communications can serve the interests of human and society.